Synergistic Effect of Dual-Doped Carbon on Mo2C Nanocrystals Facilitates Alkaline Hydrogen Evolution - Zhou, Min; Jiang, Xiaoli; Kong, Weijie; Li, Hangfei; Lu, Fei; Zhou, Xin; Zhang, Yagang (Nano-Micro Letters, 2023)
Molybdenum carbide (Mo2C) materials are promising electrocatalysts with potential applications in hydrogen evolution reaction (HER) due to low cost and Pt-like electronic structures. Nevertheless, their HER activity is usually hindered by the strong hydrogen binding energy. Moreover, the lack of water-cleaving sites makes it difficult for the catalysts to work in alkaline solutions. Here, we designed and synthesized a B and N dual-doped carbon layer that encapsulated on Mo2C nanocrystals (Mo2C@BNC) for accelerating HER under alkaline condition. The electronic interactions between the Mo2C nanocrystals and the multiple-doped carbon layer endow a near-zero H adsorption Gibbs free energy on the defective C atoms over the carbon shell. Meanwhile, the introduced B atoms afford optimal H2O adsorption sites for the water-cleaving step. Accordingly, the dual-doped Mo2C catalyst with synergistic effect of non-metal sites delivers superior HER performances of a low overpotential (99 mV@10 mA cm−2) and a small Tafel slope (58.1 mV dec−1) in 1 M KOH solution. Furthermore, it presents a remarkable activity that outperforming the commercial 10% Pt/C catalyst at large current density, demonstrating its applicability in industrial water splitting. This study provides a reasonable design strategy towards noble-metal-free HER catalysts with high activity. Highlights: 1 The B and N dual-doped carbon layer that encapsulated on Mo2C nanocrystals (Mo2C@BNC) were fabricated for accelerating HER under alkaline condition. 2 Theoretical calculations reveal that the H2O could be decomposed spontaneously over the introduced B sites, and the defective C atoms in the dual-doped carbon layer provide the best H binding sites. 3 The optimized dual doped Mo2C catalyst with synergistic effect of non-metal sites delivers superior HER performances.